Global hunger index 2022 - methodological clarifications and fresh insights - Choudhary, Neetu (Economic and Political Weekly)
At first, the arguments put forward by the government to question India$1 (Bs GHI 2022 ranking appear technically valid. However, being founded on narrow conceptual considerations, they are insufficient to defend India$1 (Bs position. While India$1 (Bs GHI ranking is affected also by the performance of other countries, the GHI score shows consistent deterioration since 2015, except in 2020. A preliminary assessment of data indicates that India$1 (Bs GHI ranking should not be seen in isolation and instead is likely a manifestation of absolute increase in urban hunger.- Reproduced s